THE USE OF INTERACTIVE METHODS IN THE FORMATION OF THE STUDENT'S ECOLOGICAL THINKING IN THE TEACHING OF "NATURAL SCIENCE" IN THE IV GRADE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, stated the use of interactive methods in the formation of the student's ecological thinking in the teaching of "Natural Science" in the IV grade, the students of general education schools from the science of science, the interdependence of society and nature, the process of ecologicalization of the educational process, the study of the ecological competence of the students of the IV grade, several tasks of the research process.